Answer: first option.
Explanation:
Given the expression:
![a+(- b)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9q920vnymlwu1uyg34cq284n777u8sdg1f.png)
You need to remember the multiplication of signs:
![(+)(+)=+\\(-)(-)=+\\(-)(+)=-](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m7bvasnei1uugzdtqp5bhqyz6a6ya87kti.png)
Then, you know that:
![a+(- b)=a-b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ua6wnk0p2mnrvacmbi2zngiipvldernide.png)
So, an equivalent expression must have
and
. Let's check the expressions provided in the options:
![(- b ) + a=-b+a \\\\b + (-a)=b-a \\\\(-a ) + b=-a+b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/50j7u0n6dks6vdmvsemfpzzb3rgdlewsox.png)
You can observe that the equativalent expression is:
![(- b ) + a](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ajmyn7owl6lfmkiiqzo8vkj8bvy2stk7gr.png)